More interest in credit - Houngbo, Emile N. (Technical Centre for Agricultural and Rural Cooperation, 1998)
Emile N. Houngbo, a socio-economist in Benin, comments on the article in Spore 71 (page 4), because the details given do not, in his opinion, match the everyday realities of the street banking sector in Benin. 'Deposits are made on a daily basis; in...